Avaliação, através da microscopia eletrônica de varredura, da limpeza de canais radiculares instrumentados pela técnica manual, ultra-sônica ou combinação de ambas, coadjuvadas por alguns agentes irrigadores - Pinto, Sérgio Araújo Holanda (1987)
The purpose of this work is to evaluare the root canal preparation effectiveness of hand and ultrasonic instru mentation techniques and hand technique followed by final ultra sonication with a smooth instrument, as well the effects or irrj_ gations Solutions such as Tergentol, Milton and Endo-PTC. Ninety recently extracted human canines were used for this study. In hand instrumentation, thirty teeth were instru mented by the step-back technique, having a file = 40 as a memory and file = 60 as final instrument. In the ultrasonic instrumen- tation trhity teeth were instrumented inicially with a file = 15 and then, the preparation was made by = 1 5, = 20, = 25 , uj_ trasonically energized K-type files during 1,5 minute each one. In the hand/u1trasonic technique thirty teeth were treated like those in the hand preparation group, except that an ultrasoni- cally energized smooth instrument was used following completion of hand technique for one minute. At the end preparation, the teeth were 1ongitudina 1ly sectioned and prepared for scanning electron microscope analysis.